(untitled) (Third Sector Social Economic Review, 2026)
Employees are the most crucial production factor in organizations, particularly because they are open to development under appropriate tools and conditions. The widespread use of information technologies has further increased the importance of sustainable motivation and organizational commitment among employees in organizations, which operate as socio-technical systems. Motivation is examined under two sub-dimensions: intrinsic and extrinsic. Intrinsic motivation is distinguished by the fact that it enables employees to be motivated without external rewards and serves as the strongest driving force behind employee attitudes and performance. Özellikle benzer görev tanımları olan bankacılık ve sigorta sektöründeki 387 katılımcıdan elde edilen veriler IBM SPSS 23 paket programı ve Microsoft Excel 2010 kullanılarak nicel araştırma yöntemi ile analiz edilmiştir. Araştırmanın bulgularına göre içsel ve dışsal motivasyon değişkenleri ile duygusal, devam ve normatif bağlılık arasında anlamlı ve pozitif yönde ilişkiler vardır. Ancak içsel motivasyon ile duygusal bağlılık arasında bir ilişki tespit edilememiştir. Bu tespitin ilgili alandaki gelecekteki çalışmalar için katkı getireceği düşünülmektedir. Özellikle hizmet odaklı bu sektörlerdeki içsel ve dışsal motivasyon boyutlarının ayrı ayrı çalışılması araştırmanın özgünlüğünü oluşturmaktadır.